2015 Portland International Conference on Management of Engineering and Technology (PICMET) 2015
DOI: 10.1109/picmet.2015.7273189
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of big data initiatives

Abstract: There is a great enthusiasm with the prospect of big data among business and industry leaders, academia and researchers. A lot of big data tools and technologies have emerged recently to capture, store, process and analyze big data. One remarkable achievement is that a handful of open source technologies have been introduced by Apache Hadoop Foundation that allows any organization to undertake big data projects. Many big data projects have been implemented during the last few years. This paper explores the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…In order to gain a competitive advantage (Kumar et al, 2011;Brentani & Droge, 1988), laptop companies must keep up with the rapid technological change (Rahman et al, 2013) occurring in this field and take strategic business decisions accordingly. Laptop manufacturing companies need to capitalize on the market by focusing on the development of new products that are offered and sold to the consumer.…”
Section: Discussionmentioning
confidence: 99%
“…In order to gain a competitive advantage (Kumar et al, 2011;Brentani & Droge, 1988), laptop companies must keep up with the rapid technological change (Rahman et al, 2013) occurring in this field and take strategic business decisions accordingly. Laptop manufacturing companies need to capitalize on the market by focusing on the development of new products that are offered and sold to the consumer.…”
Section: Discussionmentioning
confidence: 99%
“…A metadata structure scheme is a set of metadata elements that together form a structured container to which data values describing an information resource are added (Park and Tasoka, 2010). Machine readable cataloguing (MARC), Unqualified Dublin Core (DC), Qualified DC, Metadata Encoding and Transmission Standard, Metadata Object Description Schema, Moving picture experts group-21, Encoded Archival Description (EAD), Preservation Metadata: Implementation Strategies and electronic theses and dissertations are among the schemes widely used in academic libraries in the USA, the United Kingdom, Africa and elsewhere, according to studies (Park and Tosaka, 2010;Rahman et al, 2012Rahman et al, , 2013Yañez, 2009). Furthermore, Ma (2007) reported that the MARC format is the most widely used metadata schema (91%), followed by EAD (84%), Unqualified DC (78%) and Qualified DC (67%), in her Association of Research Libraries (ARL; including academic libraries) survey in the USA.…”
Section: Metadata Structure Schemesmentioning
confidence: 99%
“…With the advent of commodity hardware (to process big data), computer processing power (thanks to Moore's Law), the maturity of computer and software engineering, network bandwidth, increasingly low cost of data storage, companies are able to capture, process, transform and analyze a large volume of data. Advances in computer technology and software, new sources of data (e.g., social media), and business opportunities have created the current interest and opportunities in big data analytics (Rahman & Aldhaban, 2015;Watson, 2014).…”
Section: Introductionmentioning
confidence: 99%